Informal caregivers: conceptions about the HIV- seropositive adult children care - Ferreira, Marina Simões Flório; Figueiredo, Marco Antonio de Castro; Souza, Licia Barcelos de (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: the health care strategies have been going through constant reformulations regarding the attendance of HIV- seropositive people, due to changes in the epidemiological profile, the advances in treatment and consequent psychosocial needs that emerge from new care practices. Objective: considering the informal caregivers participation in the HIV - seropositive people care in the domestic context, the purpose of this study was to investigate the conceptions that seropositive adult children caregivers develop about the disease and the coping possibilities. Methods: individual and semi-structured interviews investigated, in depth, the four mothers experience in the home care. The interviews contents were analyzed and organized into thematic categories. Results: the contents summary allowed the understanding of meanings attributed by these mothers to the effects of physical and emotional burden required for the care, besides signal the importance of the family and professional support network and also the recognition of knowledge time about the diagnosis for the receptiveness of care needs. Conceptions about the coping with contamination risks and fear in the home environment were also identified. Conclusion: the results set supports the discussion about expanding possibilities of HIV- seropositive people care, in view of their families inclusion in the care processes and an effective integral care promotion in the health field.